Edukasi Pengolahan Sampah Organik di SMK Bina Insan Mandiri Srengseng Jakarta Barat - Popy Yuliarty; Hayu Kartika; Saruni Dwiasnati; Aulia Naro; Atiek Ike Wijayanti (CV. IRA PUBLISHING, 2026)
Bina Insan Mandiri Islamic Vocational High School has more than 30 years of experience in assisting parents in educating their children through a curriculum that reflects the distinctive characteristics of a modern Islamic school. This activity was initiated in response to the school environment, which generates considerable organic waste from daily activities. The program aimed to provide insight into organic waste management. The target participants of this activity were students of Bina Insan Mandiri Vocational High School, with the objective of providing education and training on the importance of awareness in managing organic waste. The outcomes of this activity included the production of organic fertilizers in both liquid and solid forms for plant cultivation. The outputs of this program consisted of publications in a community service journal, publications in mass media, and a video uploaded to the LPPM UMB YouTube channel. The activity evaluation was conducted by distributing questionnaires to 28 participants. The results showed an expectation score of 4.1 and a performance score of 4.33 on a 5-point scale, indicating the activity was rated satisfactory.